The Impacts of Hill Punai Aquatic Center Towards The Villagers In Kenagarian Pelangai Kaciak, Ranah Pesisir Subdistrict - HURMAYENI, NIA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Erita, Yeni (STKIP PGRI Sumbar, 2014)
Abstracts Hill Punai Aquatic Center opened in 2006, used to fumction as a car stop. Before its opening, a restaurant had been there and hill Punai Aquatic Center is located in the village of Baliak Koto Kenagarian Pelangai Kaciak, Ranah Pesisir subdistrict roadside cross Padang and Bengkulu. This study aimed to obtain information, analyzing the impact on attraction Hill Baths Punai gained from the community around the village Baliak Koto Kenagarian Pelangai Kaciak, Pesisir Selatan District viewed from 1) economic development, 2) damage to the environment, and 3) the commercialization of culture.This study is a qualitative research, conducted Hiil Punai Aquatic Center Kenagarian Pelangai Kaciak Pesisir Selatan District. Informants were taken by purposive, the people living arounnd the Mount not gained attraction Punai baths. Data were collected through interviews, observation and documentation. Data analysis was done by using data reduction, data display, data interpretation and conclusion. The results show: 1) The impact Hill Punai Aquatic Cente from the economic development community Punai seen around the village of Baliak Koto Kenagarian Pelangai Kaciak, seen from the changes in livelihood, the growths of sidejobs, 2) impact of Hill Punai Aquatic Center gained from Punai seen from the garbage strewn when visitors crowded. This leads to less clean environment and and 3) Impact of Hill Punai Aquatic Center gained from Punai views of culture villages in community Baliak Koto Kenagarian Pelangai Kaciak, seen from the changes in behavior and norms of social interaction, esecially the youths.